PENGARUH KOMPETENSI, IKLIM ORGANISASI, DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI (STUDI KASUS PADA DINAS SYARIAT ISLAM KABUPATEN BENER MERIAH) - Indah, Yusmika; Efendi, Muhsin (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
he purpose of this research is to know the influence : 1) Competence to productivity of employee at Dinas Syariat Islam Kabupaten Bener Meriah, 2) Organizational climate to productivity of employee at Dinas Syariat Islam Kabupaten Bener Meriah, 3) Motivation to productivity of employee at Dinas Syariat Islam Kabupaten Bener Meriah, 4) Competence, Organizational climate, and Motivation to productivity of employee at Dinas Syariat Islam Kabupaten Bener Meriah. The population is the research were all employee at Dinas Syariat Islam Kabupaten Bener Meriah as much as 44 employee and all it become sample. The sample strategy employee in this research using saturate sampling. Methods og data collection using questionnaire. Futher testing validity and reliability. Analysis techniques used is multiple linier regression. The result this research was showed that : 1) Competence have a positive and significant effect to productivity of employee at Dinas Syariat Islam Kabupaten Bener Meriah, 2) Organizational climate have a positive and significant effect to productivity of employee at Dinas Syariat Islam Kabupaten Bener Meriah, 3) Motivation have a positive and significant effect to productivity of employee at Dinas Syariat Islam Kabupaten Bener Meriah, 4) Competence, Organizational climate and Motivation have a positive and signific productivity of employee at Dinas Syariat Islam Kabupaten Bener Meriah.